Diversifikasi Pendanaan: Dampak pada Kinerja Bank Umum Syariah di Indonesia: Funding Diversification: Impact on the Performance of Islamic Commercial Banks in Indonesia - Afdhal Yaman; Mohammad H. Holle (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
Abstract: The implementation of the diversification strategy carried out by banks and how it impacts performance has become an exciting issue for academics and management practitioners to discuss because the final result of implementing the strategy is still debatable whether it can bring benefits or otherwise harm banking performance. Islamic banks, as banks that are still in the stage of development, have more significant potential to benefit from implementing a diversification strategy. This study aims to examine the effect of diversification on the performance of Islamic commercial banks in Indonesia, especially funding diversification during the 2010-2020 period. Sources of data were obtained from the official website of the Financial Services Authority www.ojk.go.id, and every Islamic commercial bank. Panel data analysis was used to regress the variables in this study. The cost to income ratio (BOPO) represents cost efficiency as a proxy for measuring the performance of Islamic commercial banks. The size of the bank, which is interacted with the diversification of funding, is used as a moderating variable. This study shows that the effect of funding diversification on Islamic commercial banks is positive and significant, and there is an interaction between bank size and funding diversification that affects the performance of Islamic commercial banks in the opposite direction. Keywords: Diversification; Adjusted Hirshmann-Herfindahl index; Cost-efficiency. Abstrak: Penerapan strategi diversifikasi yang lakukan oleh perbankan dan bagaimana dampaknya terhadap kinerja telah menjadi isu yang menarik bagi para akademisi maupun praktisi manajemen untuk dibahas karena hasil akhir dari penerapan strategi tersebut masih diperdebatkan apakah dapat membawa manfaat atau sebaliknya berdampak negatif terhadap kinerja perbankan. Bank syariah sebagai bank yang masih dalam tahapan untuk berkembang memiliki potensi yang lebih besar untuk memperoleh manfaat dari penerapan strategi diversifikasi. Tujuan dari penelitian ini adalah menguji pengaruh diversifikasi terhadap kinerja bank umum syariah di Indonesia khususnya diversifikasi pendanaan selama periode tahun 2010-2020. Sumber data diperoleh dari laman resmi Otoritas Jasa Keuangan www.ojk.go.id dan setiap bank umum syariah. Analisis data panel digunakan sebagai metode dalam meregresi variabel-variabel pada penelitian ini. Rasio biaya terhadap pendapatan (BOPO) merepresentasikan efisiensi biaya sebagai proksi pengukuran kinerja bank umum syariah. Ukuran bank yang diinteraksikan dengan diversifikasi pendanaan digunakan sebagai variabel moderasi. Hasil penelitian ini memperlihatkan bahwa pengaruh diversifikasi pendanaan terhadap bank umum syariah adalah positif signifikan dan terdapat interaksi antara ukuran bank dengan diversifikasi pendanaan yang memengaruhi kinerja bank umum syariah secara berlawanan. Keywords: Diversifikasi; Adjusted Hirshmann-Herfindahl Index; Efisiensi Biaya.